DOES CONCENTRATED OWNERSHIP MATTER? MODERATING THE LINK BETWEEN LIQUIDITY AND CSR - Mutmainnah Mutmainnah; Nur Asni; Muhammad Zaikin; La Ode Muhammad Saum Fasihu; Sindy fuji Lestari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
With ownership concentration acting as a moderating variable, this research investigates the relationship between working capital efficiency measured by the cash conversion cycle (CCC) and CSR performance in light of the importance of CSR activities in sustainable business strategies. Panel regression in STATA 17 was used to analyze 162 non-financial companies listed on the Indonesia Stock Exchange between 2018 and 2023 using purposive selection. The findings indicate that ownership concentration exacerbates this negative relationship, whereas a shorter CCC (more liquidity) enhances CSR performance. The results show that working capital management is linked to financial efficiency and is a strategic instrument for establishing long-term legitimacy and complying with regulatory obligations. The research emphasizes how important it is for management, stakeholders, and regulators to assess ownership structure and liquidity in order to promote sustainable business practices, especially in developing markets like Indonesia.